Totalitarian dictatorship and autocracy / Carl J. Friedrich and Zbigniew K. Brzezinski - Brzezinski, Zbigniew; Friedrich, Carl J. (Carl Joachim) (Praeger University Series. Political Science)
Bibliografía: p. 315-336. Índices